Variational Iteration Method and Differential Transformation Method for Solving the SEIR Epidemic Model - A. Harir; S. Melliani; H. El Harfi; L. S. Chadli (International Journal of Differential Equations)
The aim of the present study is to analyze and find a solution for the model of nonlinear ordinary differential equations (ODEs) describing the so-called coronavirus (COVID-19), a deadly and most parlous virus. The mathematical model based on four nonlinear ODEs is presented, and the corresponding numerical results are studied by applying the variational iteration method (VIM) and differential transformation method (DTM).